Enhancing Circular Economy with Digital Technologies: A PLS-SEM Approach - Williams, Jack; Prawiyogi, Anggy Giri; Rodriguez, Miguel; Kovac, Ivan (Pandawan Sejahtera Indonesia, 2024)
This study investigates the transformative potential of the digital economy in fostering the principles of a circular economy. Utilizing the SmartPLS methodology, we explore key determinants that drive the transition towards a sustainable economic framework and assess their impacts on both environmental sustainability and economic resilience. Our analysis highlights that the integration of digital technologies, such as IoT, blockchain, and AI, within circular economy practices can significantly enhance resource efficiency, reduce waste, and promote sustainable economic growth. These technologies enable better tracking and management of resources, facilitating closed-loop systems that are essential for a circular economy. However, our findings also identify substantial challenges, including concerns over data security, digital divide, and unequal access to advanced technologies, which may hinder the equitable distribution of benefits. The study underscores the importance of an integrated policy approach that combines technological innovation with supportive regulatory frameworks to address these challenges and maximize the benefits of digital integration. Policymakers are encouraged to develop strategies that not only foster technological advancements but also ensure inclusive access and address security issues. This research provides comprehensive insights for stakeholders, including governments, businesses, and academia, in designing effective strategies and policies aimed at promoting a sustainable circular economy in the digital era. By aligning digital advancements with circular economy principles, we can pave the way towards achieving sustainable development goals and creating a resilient economic future.